Effect of biocides on S. cerevisiae: relationship between short-term membrane affliction and long-term cell killing - Chládková, K; Hendrych, T; Gásková, D; Goroncy-Bermes, P; Sigler, K (Folia microbiologica, 2004)
The long-term action of recommended (RC) and near-recommended concentrations of several commercial biocides (Lonzabac 12.100, Genamin CS302D, benzalkonium chloride and 2-phenoxyethanol) on cells of S. cerevisiae wild-type strain DTXII was described using plating tests while short-term effects were determined using the potentiometric fluorescent probe diS-C3(3) that detects both changes in membrane potential and impairment of membrane integrity. A 2-d plating of cells exposed to 0.5xRC of benzalkonium chloride and Genamin CS302D for 15 min showed a complete long-term cell killing, with 2-phenoxyethanol the killing was complete only at 2xRC and Lonzabac caused complete killing at RC but not at 0.5xRC. The diS-C3(3) fluorescence assay performed immediately after a 10-min biocide exposure revealed several concentration-dependent modes of action: Lonzabac at 0.5xRC caused a mere depolarization, higher concentrations causing gradually increasing cell damage; benzalkonium chloride and Genamin CS302D rapidly damaged the membrane of some cells and depolarized the rest whereas 2-phenoxyethanol, which had the lowest effect in the plating test, produced a concentration-dependent fraction of cells with impaired membranes. Cell staining slightly increased during the diS-C3(3) assay; addition of a protonophore showed that part of the remaining undamaged cells retained their membrane potential. Comparison of short-term and long-term data implies that membrane depolarization alone is not sufficient for complete long-term killing of yeast cells under the action of a biocide unless it is accompanied by perceptible impairment of membrane integrity. The results show that the diS-C3(3) fluorescence assay, which reflects the short-term effects of a biocide on cell membranes, can be successfully used to assess the microbicidal efficiency of biocides.
Keywords: Benzalkonium Compounds; membránové potenciály; Carbocyanines; fluorescenční spektrometrie; Cell Membrane; Spectrometry, Fluorescence; Membrane Potentials; karbocyaniny; Cell Membrane Permeability; permeabilita buněčné membrány; Microbial Sensitivity Tests; fluorescenční barviva; mikrobiální testy citlivosti; Anti-Infective Agents; antiinfekční látky; Fluorescent Dyes; buněčná membrána; benzalkoniové sloučeniny; Saccharomyces cerevisiae; ethylenglykoly; Ethylene Glycols